2022
DOI: 10.1037/xge0000833
|View full text |Cite
|
Sign up to set email alerts
|

When the eyes have it and when not: How multiple sources of activation combine to guide eye movements during multiattribute decision making.

Abstract: Memory plays a major but underexplored role in judgment and decision making (JDM). Studying eye movements-especially how people look at empty spatial locations when retrieving from memory information previously associated with those locations-provides useful information about how memory influences JDM. This so-called looking-at-nothing behavior is thought to reflect memory-driven allocation of attention. However, eye movements are also guided toward salient visual stimuli, such as test items presented on a scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 95 publications
(225 reference statements)
2
4
0
Order By: Relevance
“…Experiment 2 replicated the finding for preferential judgments and ruled out the alternative hypothesis that the observed eye-movement effects occurred only because participants were instructed to respond as consistently as possible. These findings are in line with previous research showing that as the similarity between training and test items increases, people proportionally look more to the associated but emptied spatial locations (Rosner et al, 2022;Rosner & von Helversen, 2019;Scholz et al, 2015). However, does this similarity effect on eye movements mean that people retrieve information about exemplars from memory?…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Experiment 2 replicated the finding for preferential judgments and ruled out the alternative hypothesis that the observed eye-movement effects occurred only because participants were instructed to respond as consistently as possible. These findings are in line with previous research showing that as the similarity between training and test items increases, people proportionally look more to the associated but emptied spatial locations (Rosner et al, 2022;Rosner & von Helversen, 2019;Scholz et al, 2015). However, does this similarity effect on eye movements mean that people retrieve information about exemplars from memory?…”
Section: Discussionsupporting
confidence: 91%
“…The goal of this study was to test whether exemplar retrieval also occurs during preferential judgments and to link eye movements to preferential judgments. Eye-movement measures based on the lookingat-nothing behavior have been shown to indicate exemplar retrieval from memory during inferential choice (Rosner et al, 2022;Rosner & von Helversen, 2019;Scholz et al, 2015). In line with previous research, we found that the amount people looked at empty spatial locations reflected the similarity (defined as a number of matches in cue values) between test items and training exemplars.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Studies have suggested that the reenactment of eye movements and the tendency to re-fixate the locations where targets were previously presented during retrieval serves a functional role in enhancing memory performance (Laeng et al, 2014; Rosner et al, 2022; Scholz et al, 2016, 2018). This view was supported by a study by Johansson & Johansson (2014), in which participants were asked to memorize the orientation and spatial location of objects and were later tested on them.…”
Section: Introductionmentioning
confidence: 99%